Portugal on the eve of presidential elections - N. M. Yakovleva (Ибероамериканские тетради, 2021)
In 2015, Portugal entered a new political cycle with the main actors being the left-wing parties under the auspices of the Socialist Party and its leader Antonio Costa who took over as prime minister. The author analyzes the results of the socialist government activities carried out with the parliamentary support of the left. The author also studies the electoral process of 2017-2019, the dynamics of strengthening the position of the Socialist Party, and significance of the results of elections to national authorities. The trajectory of the country’s membership in the European Union, the history of the results of the European Parliament elections, including the 2019 elections, and the positions of the main political parties are analyzed. In connection with force majeure circumstances arising from the COVID-19 pandemic, the situation in the healthcare system was also studied and a program of the authorities to prevent the spread of coronavirus infection is presented in the article. The author touches upon the economic consequences of the pandemic, especially on those industries that will be most affected – tourism in particular. The article contains a brief forecast of the alignment of political forces on the eve of the presidential elections in 2021. The key is the idea that the pandemic will make possible adjustments in terms of the image and ratings of the country’s leaders and other participants in the election race. While presidential election results are usually a foregone conclusion in the event that a current head of state runs for a second term (as it is shown in the brief historical overview leading up to the article), the prime minister’s growing leadership can make adjustments to the final outcomes.